Respuesta :

LIMASH

Answer:p= -18

Step-by-step explanation:Let's solve your equation step-by-step.

5/4 P= 4/3 P + 3/2

Step 1: Subtract 4/3p from both sides.

5/4 P - 4/3 P = 4/3 P + 3/2 - 4/3 P

-1/12 P = 3/2

Step 2: Multiply both sides by 12/(-1).

(12/-1) × (-1/12 P) = (12/-1) × (3/2)

P = -18

Answer:

p = - 18

Step-by-step explanation:

5        4          3

--- p =  --- p + ---

4         3         2

5        2²          3

--- p =  --- p + ---

2²         3         2

5p     2² * p       3

---  =  ---------  +  ---

2²          3          2

p = - 18

ACCESS MORE